Plasmon-enhanced photoresponse of single silver nanowires and their network devices - Razeghi, Mohammadali (2022)
The photo-bolometric effect is critically important in optoelectronic structures and devices employing metallic electrodes with nanoscale features due to heating caused by the plasmonic field enhancement. One peculiar case is individual silver nanowires (Ag NWs) and their networks. Ag NW-networks exhibit excellent thermal, electrical, and mechanical properties, providing a simple yet reliable alternative to common flexible transparent electrode materials used in optoelectronic devices. To date, there have been no reports on the photoresponse of Ag NWs. In this study, we show that single Ag NWs and networks of such Ag NWs possess a significant, intrinsic photoresponse, thanks to the photo-bolometric effect, as directly observed and measured using scanning photocurrent microscopy. Surface plasmon polaritons (SPPs) created at the contact metals or plasmons created at the nanowire-metal structures cause heating at the junctions where a plasmonic field enhancement is possible. The local heating of the Ag NWs results in negative photoconductance due to the bolometric effect. Here an open-circuit response due to the plasmon-enhanced Seebeck effect was recorded at the NW-metal contact junctions. The SPP-assisted bolometric effect is found to be further enhanced by decorating the Ag NWs with Ag nanoparticles. These observations are relevant to the use of metallic nanowires in plasmonic applications in particular and in optoelectronics in general. Our findings may pave the path for plasmonics-enabled sensing without spectroscopic detection.